1996
DOI: 10.1093/infdis/173.6.1493
|View full text |Cite
|
Sign up to set email alerts
|

Diphtheria Antitoxin Levels in US Blood and Plasma Donors

Abstract: Plasma samples from 500 blood donors were titrated for diphtheria antitoxin (DAT) by the toxin neutralization (TN) test. Only 1.6% of donors had <0.01 IU/mL DAT, the minimum protective level against diphtheria; 15% had levels between 0.01 and <0.1 IU/mL, indicating basic protection, and 83.4% had levels > or =0.1 IU, indicating full protection. Three hundred fifty samples were studied by ELISA for diphtheria toxoid IgG antibodies to assess the utility of the assay as a quick, convenient method for evaluating d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Patients were classified according to internationally accepted criteria of protective antibody levels (8)(9)(10)(11)(12). Tetanus and diphtheria antibody concentrations lower than 0.01 IU/mL were considered to indicate the absence of protection, between 0.01 and 0.09 IU/mL were considered to indicate basic immunity, and values of 0.1 IU/mL or higher were considered to indicate full protection.…”
Section: Methodsmentioning
confidence: 99%
“…Patients were classified according to internationally accepted criteria of protective antibody levels (8)(9)(10)(11)(12). Tetanus and diphtheria antibody concentrations lower than 0.01 IU/mL were considered to indicate the absence of protection, between 0.01 and 0.09 IU/mL were considered to indicate basic immunity, and values of 0.1 IU/mL or higher were considered to indicate full protection.…”
Section: Methodsmentioning
confidence: 99%
“…Although such methods measure antibodies directed against nontoxic epitopes of the toxin molecule, they exhibit a high correlation with results obtained by toxin neutralization assays for samples with antitoxin levels of ≥ 0.1 IU/ml. However, there is a low correlation when the antitoxin titers are < 0.1 IU/ml [2,9]. In that respect, our assay does not differentiate individuals having DAT values of 0.01-0.1 IU/ml (basically protected) from those with titers of < 0.01 IU/ml (susceptible), and it is suggested that all persons with values of < 0.1 IU/ml are not sufficiently protected.…”
Section: Discussionmentioning
confidence: 63%
“…In the developed countries, widespread vaccination of infants and young children began several decades ago and proved to provide high rates of immunity in these agegroups [2]. However, in such regions, it has been shown that diphtheria immunity is waning among adult populations who were given only basic childhood immunization.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the negative anti-diphtheria antibody titers, by ELISA, the authors [16] utilized the Vero cell neutralization test; when these two tests (ELISA and Vero cell neutralization) were used, the seropositivity rate rose from 64.4% to 90.3%. This suggests that the large fall in anti-diphtheria antibodies observed immediately prior to the booster dose was mainly due to the serological method utilized, since the neutralization test has greater sensitivity for detecting the immunological response for diphtheria when the antibody titer is less than 0.1 IU/ mL and therefore ELISA underestimates the seroprotection rate for this group [17]. The large increase in concentrations of these two antibodies that occurred after the booster dose, in relation to the concentrations found immediately before this dose, was also found in an American study [16].…”
Section: Discussionmentioning
confidence: 99%